2014
DOI: 10.1136/bmjspcare-2014-000654.276
|View full text |Cite
|
Sign up to set email alerts
|

An Audit Into Advanced Care Planning for End of Life Care Patients at Kingston Hospital

Abstract: Background The End-of-Life Care (EoLC) Strategy 2008 highlighted the importance of early identification of potential for dying and Advanced Care Planning (ACP).1 2 3 Early awareness of poor prognosis helps patients and their relatives to understand their illness and make informed choices about their care; for instance whether to decline aggressive intervention and hospitalisation if it is unlikely to improve their quality of life. Aims and Objectives To prompt early communication within the MDT and with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similar ACP audits have been used at Kingston Hospital, UK, which found that implementation of an ACP summary and JMO teaching sessions improved resuscitation status, prognosis, ceilings-of-care and readmission status documentation in medical notes and at discharge. 5 The documentation of advance care planning preferences of RACF patients in our hospitals was suboptimal. Our audit tool can be used to improve advance care planning between RACF and hospital setting.…”
mentioning
confidence: 97%
“…Similar ACP audits have been used at Kingston Hospital, UK, which found that implementation of an ACP summary and JMO teaching sessions improved resuscitation status, prognosis, ceilings-of-care and readmission status documentation in medical notes and at discharge. 5 The documentation of advance care planning preferences of RACF patients in our hospitals was suboptimal. Our audit tool can be used to improve advance care planning between RACF and hospital setting.…”
mentioning
confidence: 97%